Pengaruh Disiplin Kerja dan Stres Kerja terhadap Kepuasan Kerja Pegawai pada Direktorat Pemberdayaan Masyarakat Transmigrasi Kementerian Transmigrasi RI - Afifatul Wulandari; Suryanto Sosrowidigdo; Siti Nurjanah (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study aims to analyze the influence of work discipline and work stress on employee job satisfaction at the Directorate of Transmigration Community Empowerment, Ministry of Transmigration of the Republic of Indonesia. The study employs a quantitative approach using an associative method. The sample consists of 30 employees, selected using the saturated sampling technique. Data were collected via questionnaires and analyzed using IBM SPSS Statistics 20, incorporating validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results indicate that work discipline has a positive but insignificant effect on employee job satisfaction, with a t-value of 0.299 and a significance level of 0.767. Conversely, work stress has a negative and significant effect on job satisfaction, with a t-value of -3.011 and a significance level of 0.006. Simultaneously, both variables significantly influence job satisfaction, with an F-value of 4.999. The R-square value of 0.270 indicates that the model explains 27% of the variation in employee job satisfaction.